2021
DOI: 10.1027/1016-9040/a000462
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in COVID-19 Preventive Behavior

Abstract: Abstract. Age is a critical risk factor for severe COVID-19. This is mirrored by older people showing preventive health behaviors more frequently. However, collective action across all age groups is necessary to reduce transmission. Therefore, this study assessed whether age differences are moderated by policy changes and whether policies further moderate the relationship between psychological determinants of behavior (risk perceptions and trust), age, and preventive behaviors. Risk perceptions, trust in insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 74 publications
2
13
0
Order By: Relevance
“…In the present study, more than half of the university students (60.3%) had been in contact with a person infected by COVID-19 and furthermore, 28.6% indicated having been infected by COVID-19. This may be because at the time of the study, the pandemic had been going on for a year and a half and more and more people were infected or because young people have been infected more than older people [ 33 ], so that many participants have been in contact with COVID-19-infected person.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, more than half of the university students (60.3%) had been in contact with a person infected by COVID-19 and furthermore, 28.6% indicated having been infected by COVID-19. This may be because at the time of the study, the pandemic had been going on for a year and a half and more and more people were infected or because young people have been infected more than older people [ 33 ], so that many participants have been in contact with COVID-19-infected person.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one study found a link between genders and mask use in terms of pain and irritation of the skin, ears, nose, and mouth, among other things [ 35 ]. Or another indicated that age differences have a significant impact on COVID-19 protective behaviors, even after mandatory policies were implemented [ 36 ]. As a result, to achieve high adherence, the importance of preventive behaviors must be well understood, especially in young people who are less directly threatened by the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our sample showed a high willingness to adopt the behaviors, which might have resulted in an underestimation of the effects found. For instance, in countries where compliance and regulations are weaker, or at times when compliance wanes due to habituation effects, individual differences are likely to matter more [ 45 , 46 ]. Another limitation arises from the fact that we could not comply with one of the pre-registered exclusion criteria (i.e., whether one has been infected with COVID-19), and this might have affected our results.…”
Section: Discussionmentioning
confidence: 99%